IMPLEMENTATION OF LOCAL WISDOM-BASED BIOTECHNOLOGY TEXTBOOK FROM TABAGSEL REGION ON CREATIVITY AND CRITICAL THINKING SKILLS OF STUDENTS AT UNIVERSITAS MUHAMMADIYAH TAPANULI SELATAN - Melvariani Syari Batubara; Rafiqah Amanda Lubis; Elda Sari Siregar; Happy Sri Rezeki Purba; Ilmi Aulina Rahim (Universitas Negeri Medan, 2026)
The objective of this study is to determine the implementation of a Tabagsel local wisdom-based biotechnology textbook on the creativity and critical thinking abilities of students at UMTS in the biotechnology course. The method employed in this research is PTK to assess the creativity and critical thinking abilities of students at UMTS. This PTK was conducted in 2 cycles, each consisting of stages: Analysis, Fact Finding, Conceptualization, Planning, Implementation, Additional Fact Finding, and Evaluation. The results of this study indicate that the highest score on the student creativity test in cycle I was 85 and the lowest was 54. The highest score on the student creativity test in cycle II was 95 and the lowest was 75. The increase in student creativity test scores was 10 points. The number of students who achieved mastery on the creativity test in cycle I was 12 students and in cycle II was 17 students, with an increase of 5 students. The conclusions of this study are: The PKK on the student creativity test in cycle I was 50% and in cycle II was 70%, with an increase of 20%; The percentage of students who achieved mastery on the critical thinking test was 80%, while those who did not achieve mastery was 20%.